2017
DOI: 10.1111/nmo.13050
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of same day versus next day colon manometry results in children with medical refractory constipation

Abstract: Background We evaluated the change on colon manometry (CM) parameters and interpretation comparing results when the study is performed the same day after the motility catheter is placed under anesthesia or the following day. Methods CM catheter was placed with colonoscopy under anesthesia and recorded on day 1 and repeated on day 2. Study parameters including motility index (MI) during fasting, post-prandial and post-Bisacodyl challenge phase; gastrocolonic response; number, presence and propagation of high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…One of the potential study limitations is the timing of the colonic manometry in relation to the manometry catheter placement under general anesthesia. Arbizu et al and Liem et al have suggested that the results of the colonic manometry recording can differ or be improved, with regards to HAPC presence and propagation, when study is performed on the day following the catheter placement. However, in all our patients, the HAPC was present and fully propagated; therefore, we believe that the impact of the recording starting time was minimal.…”
Section: Discussionmentioning
confidence: 99%
“…One of the potential study limitations is the timing of the colonic manometry in relation to the manometry catheter placement under general anesthesia. Arbizu et al and Liem et al have suggested that the results of the colonic manometry recording can differ or be improved, with regards to HAPC presence and propagation, when study is performed on the day following the catheter placement. However, in all our patients, the HAPC was present and fully propagated; therefore, we believe that the impact of the recording starting time was minimal.…”
Section: Discussionmentioning
confidence: 99%
“…21 Similarly, we have previously demonstrated that colon manometry study parameters and interpretation changed in a substantial number of subjects from the day the motility catheter was placed endoscopically under anesthesia compared to the following day. 16 Both studies suggest a potential effect of anesthesia on intestinal motility that could affect study interpretation and suggest that when the study is abnormal, it should be repeated the day after anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Previous animal and human studies have demonstrated that anesthesia affects gastric and duodenal motility. 12,13 Furthermore, we have shown that colon motility could be affected by anesthesia and manipulation during colonoscopy, 16 which suggests that study results and interpretation might be affected if the ADM is performed the same day of anesthesia and catheter placement. Due to the increased use of ADM in pediatrics, it is important to know whether the test can be performed the same day the catheter is placed under anesthesia.…”
mentioning
confidence: 99%
“…In most institutions, the study is performed the next day to avoid anesthesia effects, and there is preliminary evidence in pediatrics that anesthesia may adversely affect digestive motility. 27 In adults diazepam has been found no to have no major effect on interdigestive antroduodenal motility. 28 Studies in healthy controls undergoing elective surgery have found that all methods of general anesthesia studied (halothane, enflurane, pethidine and fentanyl) reduced the duration of the interdigestive motility complex, mainly by reducing phase II.…”
Section: Antroduodenal Manometrymentioning
confidence: 96%
“…When anesthesia is used, pressure recording should not be started until the patient is fully awake and any potential anesthetic effects on motility have worn off. In most institutions, the study is performed the next day to avoid anesthesia effects, and there is preliminary evidence in pediatrics that anesthesia may adversely affect digestive motility …”
Section: How To Perform the Test?mentioning
confidence: 99%